Digital Learning Tools for Mobile Devices for Accomplish Hypothesis Testing of Statistical Parameters - Tapia Moreno, Francisco Javier; Villa-Martinez, Hector Antonio (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Technological changes have been associated with the evolution of computer and telecommunications systems. These changes have resulted in a rethinking of teaching and learning methods in the new digitalized environment at all educational levels. This rethinking motivates some teachers to design new digital tools that support students in their learning process, offering them an easier and more entertaining way to obtain knowledge. The digital learning tools are software and informatics programs that make everyday activities easier for students. We have designed four digital learning tools for the learning of inferential statistics that allow college students to perform hypothesis tests for: i) the arithmetic mean of the population, ii) the proportion of a population, iii) the difference between two arithmetic means, and iv) the difference between two proportions. These digital learning tools are products from the project “Statistics-to-Go” that is being developed at the University of Sonora. This project is now in its fourth stage.